2021
DOI: 10.46827/ejlll.v5i2.271
|View full text |Cite
|
Sign up to set email alerts
|

Africa in Retrospect and the Future: A Stylistic Analysis of Deviation and Parallelism in Diop’s Africa

Abstract: Attention of language scholars has been shifting from the structural pattern of language to language as a functional unit given the change of interest from the form of a language to its function. This study presents a stylistic analysis of a well-known poem by David Diop “Africa” and analyses the unique role that language plays in projecting the central theme of the poem. The poem Africa is one of the poems that laments the ill treatments that Africa suffered in the hands of its colonialists, but which quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Besides, Djorbua et al (2021), in their study, argued that Parallelism refers to a vital stylistic device applied to promote collectiveness (Djorbua et al, 2021). Then, their study revealed that Parallelism in the poem has showed the relationship that occurs between literary work and its impact on the society as a mirror of reflection (Djorbua et al, 2021). Furthermore, Mwinwelle et al (2021), in their study, stated that Parallelism can be defined as the logical connection of ideas by applying similar grammatical forms (Mwinwelle et al, 2021).…”
Section: Parallelismmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Djorbua et al (2021), in their study, argued that Parallelism refers to a vital stylistic device applied to promote collectiveness (Djorbua et al, 2021). Then, their study revealed that Parallelism in the poem has showed the relationship that occurs between literary work and its impact on the society as a mirror of reflection (Djorbua et al, 2021). Furthermore, Mwinwelle et al (2021), in their study, stated that Parallelism can be defined as the logical connection of ideas by applying similar grammatical forms (Mwinwelle et al, 2021).…”
Section: Parallelismmentioning
confidence: 99%
“…In the Snow White and the Huntsman movie, there are no found any stylistics elements of Parallelism used by the main characters. Besides, Djorbua et al (2021), in their study, argued that Parallelism refers to a vital stylistic device applied to promote collectiveness (Djorbua et al, 2021). Then, their study revealed that Parallelism in the poem has showed the relationship that occurs between literary work and its impact on the society as a mirror of reflection (Djorbua et al, 2021).…”
Section: Parallelismmentioning
confidence: 99%